Implicit Pension Debt, Transition Cost, Options, and Impact of China's Pension Reform : A Computable General Equilibrium Analysis - Wang, Yan (World Bank, Washington, DC, 2014)
The main problems with China's pension system--the pension burdens of state enterprises and the agency of the population--have deepened in recent years. Using a new computable general equilibrium model that differentiates between three types of enterprise ownership and 22 groups in the labor force, the authors estimate the effects of pension reform in China, comparing various options for financing the transition cost. They examine the impact that various reform options would have on the system's sustainability, on overall economic growth, and on income distribution. The results are promising. The current pay-as-you-go system, with a notional individual account, remains unchanged in the first scenario examined. Simulations show this system to be unsustainable. Expanding coverage under this system would improve financial viability in the short run but weaken it in the long run. Other scenarios assume that the transition cost will be financed by various taxes and that a new, fully funded individual account will be established in 2001. The authors compare the impact of a corporate tax, a value-added tax, a personal income tax, and a consumption tax. They estimate the annual transition cost to be about 0.6 percent of Gross Domestic Product (GDP) between 2000 and 2010, declining to 0.3 percent by 2050. Using a personal income tax to finance the transition cost would best promote economic growth and reduce income inequality. Levying a social security tax and injecting fiscal resources to finance the transition costs would help make the reformed public pillar sustainable. To finance a benefit of 20 percent of the average wage, a contribution rate of only 10 percent-12.5 percent would be enough to balance the basic pension pillar. Gradually increasing the retirement age would further reduce the contribution rate.